The conjugate gradient method for the adjustment of cadastral data in GIS - Buyong, Taher; Daud, Abdullah (UTM, 2001)
The use of measurements as the source of data for creating digital cadastral database supplemented by the adjustment of the measurements by the least squares method, undoubtedly results in accurate and up-to-date metric information. However the approach involves solving an extremely large system of linear equations, and subsequently increases the computing time and also requires large amount of computer processing storage. The problems are solved by applying an iterative conjugate gradient method (CGM). The proposed method reduces the storage by at least 70% compared to the prevailing usage of the banded storage scheme and significantly speed up processing time as compared to the usual Cholesky Decomposition method.